Towards Sustainable Development: Ibn Ashur's Insights on the Impact of Productive Zakat for Achieving SDGs - Citaningati, Putri Rizka (Universitas Muhammadiyah Yogyakarta, 2024)
In the Islamic community, discussions on zakat utilization often center around its most effective use. Some believe that zakat should only be distributed to the eight categories of mustahik, while scholars like Ibn Asyur suggest that zakat can be used productively when applied with the right intentions and methods. This study investigated how productive zakat can contribute to Sustainable Development Goals (SDGs), particularly supporting economic and human advancement. This study used an explanatory qualitative approach with secondary data to reconstruct the theoretical and empirical frameworks that assess the impact of zakat productive distribution by zakat amil institutions. These institutions adhere to the principles of wasilah (means) and maqsud (intention) in the productive use of zakat funds productively to Ibn Asyur's contemporary maqasid Sharia perspective. Zakat can fulfill essential human needs, benefiting both mustahik and society at large. The findings suggest that productive zakat contributes significantly to poverty reduction, health improvement, educational access, economic growth, and environmental sustainability, aligning closely with the objectives of the SDGs.